Taurine Reverses Oxidative Damages and Restores the Muscle Function in Overuse of Exercised Muscle - Thirupathi, Anand; Pinho, Ricardo A.; Baker, Julien S.; István, Bíró; Gu, Yaodong (Frontiers in Physiology, 2020)
Exercise-induced oxidative stress is linked with the expression level of endogenous antioxidants, but these antioxidants cannot overcome all oxidative stress-related damages in the cells, particularly when cells are under physiological stress. Therefore, some special compounds are needed for cellular function, which are produced/activated within the cells, and these compounds can be synthesized by performing exercise, especially high-performance exercise. Taurine is a sulfur-containing amino acid used for various physiological functions. However, its synthesis and accumulation under oxidative environment may be compromised. Recently, we have shown that taurine level is increased during exercise performance with a decrease in oxidative damage in overused muscles. Other studies have also shown that short-time supplementation with taurine increased the physiological performance during severe work intensities, suggesting the role of taurine in improving muscle performance during exercise. However, its precursor cysteine is used in the synthesis of other compounds like GSH and Coenzyme A, which are important for regulating redox system and energy homeostasis, and thus, it is important to understand whether taurine synthesis within the cells can blunt the activity of other compounds that are beneficial in preventing oxidative damages during intense exercise. Further, it is important to understand whether taurine supplementation can prevent the conditions observed in the physiological stress of muscles. Therefore, this review discusses how taurine synthesis could alter the exercise-induced ROS generation and its relationship between the physiological stress of muscle and subsequent improvements in exercise performance.